2015
DOI: 10.1371/journal.pone.0129809
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Beta-Cell Deficiency in Pancreata of Dogs with Canine Diabetes

Abstract: The pathophysiology of canine diabetes remains poorly understood, in part due to enigmatic clinical features and the lack of detailed histopathology studies. Canine diabetes, similar to human type 1 diabetes, is frequently associated with diabetic ketoacidosis at onset or after insulin omission. However, notable differences exist. Whereas human type 1 diabetes often occurs in children, canine diabetes is typically described in middle age to elderly dogs. Many competing theories have been proposed regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 42 publications
1
70
0
4
Order By: Relevance
“…In another study, histopathologic evidence of chronic pancreatitis was found in 6 of 18 diabetic dogs and acute pancreatitis was found in 5 of 18 . In contrast, other studies on diabetic dogs have found histopathologic evidence of pancreatitis to be lacking or rare . In both dogs and people, it is difficult to identify a cause and effect relationship between DM and pancreatitis, and both could result from the same primary disease process.…”
Section: Dm Secondary To Diseases Of the Exocrine Pancreas In Dogsmentioning
confidence: 95%
See 4 more Smart Citations
“…In another study, histopathologic evidence of chronic pancreatitis was found in 6 of 18 diabetic dogs and acute pancreatitis was found in 5 of 18 . In contrast, other studies on diabetic dogs have found histopathologic evidence of pancreatitis to be lacking or rare . In both dogs and people, it is difficult to identify a cause and effect relationship between DM and pancreatitis, and both could result from the same primary disease process.…”
Section: Dm Secondary To Diseases Of the Exocrine Pancreas In Dogsmentioning
confidence: 95%
“…In an earlier study, infiltrating mononuclear cells (predominantly lymphocytes) were observed in 6 of 18 dogs (33%) with DM whereas in 5 dogs (28%), extensive pancreatic damage appeared to be responsible for the development of DM . An absence or decreased numbers of islets together with degeneration and vacuolization but no inflammation was described in 3 studies evaluating pancreatic histopathology in a total of 74 diabetic dogs …”
Section: T1dm: Does Autoimmunity Cause Adult‐onset Dm In Dogs?mentioning
confidence: 99%
See 3 more Smart Citations